Exploration HOTS (Higher Order Thinking Skills) in Arabic Textbook - Yasmar, Renti; Al Husna, Lathifah; Wargadinata, Wildana Wargadinata; Nurhadi, Nurhadi (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
This study aims to explore HOTS (Higher Order Thingking Skill) in Class VIII Arabic Textbooks. This research uses qualitative descriptive methods with document analysis techniques (content analysis). The document analyzed in this study is a Class VIII MTs Arabic textbook published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020. This study concludes that HOTS problems are more complex, require deeper thinking, and often require the application of concepts in new or complex contexts. Of the 16 question commands on Tadrib Maharah Qiraah contained in 6 dars in the MTs Class VIII Arabic textbook, it was found that only 6 question commands included the cognitive level at the HOTS level with 3 categories of question commands, namely determining paragraph titles, answering questions based on text and making sentences based on images.